Hotspots and research trends of gut microbiome in polycystic ovary syndrome: a bibliometric analysis (2012–2023) - Wu, Ruishan; Mai, Zhensheng; Song, Xiaoyan; Zhao, Wenzhong (Frontiers in Microbiology, 2025)
IntroductionPolycystic ovary syndrome (PCOS) is a common gynecological condition affecting individuals of reproductive age and is linked to the gut microbiome. This study aimed to identify the hotspots and research trends within the domain of the gut microbiome in PCOS through bibliometric analysis.MethodsUtilizing bibliometric techniques, we examined the literature on the gut microbiome in PCOS from the Web of Science Core Collection spanning the period from 2012 to 2023. Analytical tools such as CiteSpace, VOSviewer, and Bibliometric R packages were employed to evaluate various metrics, including countries/regions, institutions, authors, co-cited authors, authors’ H-index, journals, co-references, and keywords.ResultsA total of 191 publications were identified in the field of gut microbiome in PCOS, with an increase in annual publications from 2018 to 2023. People’s Republic of China was the most productive country, followed by the United States of America (USA), India. Shanghai Jiao Tong University, Fudan University, and Beijing University of Chinese Medicine were the top three most publications institutions. Thackray VG was identified as the most prolific author, holding the highest H-index, while Liu R received the highest total number of citations. The journal “Frontiers in Endocrinology” published the most articles in this domain. The most frequently co-cited reference was authored by Qi XY. The analysis of keyword burst detection identified “bile acids” (2021–2023) as the leading frontier keyword. Additionally, “gut dysbiosis,” “phenotypes,” “adolescents,” “metabolomics,” “metabolites,” “fecal microbiota transplantation,” and “IL-22” have emerged as the primary keywords reflecting recent research trends.ConclusionThis bibliometric analysis explores how the gut microbiome influences endocrine and metabolic disorders related to PCOS, emphasizing its role in the development of PCOS and treatments targeting the gut microbiome. The findings serve as a valuable resource for researchers, enabling them to identify critical hotspots and emerging areas of investigation in this field.